Phase-change heat storage fiber with composite structure and preparation method thereof
By embedding high-entropy vanadium-based shell phase change nano microcapsules in polymer fibers, the composite structure of phase change heat storage fibers is formed, which solves the problem of structural instability of existing phase change microcapsules at high temperatures, and achieves the effect of high strength and high phase change enthalpy, which is suitable for heat storage and energy storage applications.
Patent Information
- Application Number
- CN202311072321.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-08-24
AI Technical Summary
The existing phase-change microcapsules are difficult to maintain their structural stability under high temperature conditions and cannot be effectively applied to melt spinning processes.
High-entropy vanadium-based shell phase-change nano-microcapsules are used to design the composite material of the core-shell structure and uniformly embedded in the polymer fiber matrix to form the phase-change heat storage fiber of the composite structure.
Under high temperature conditions of 200~300℃, the phase change fiber maintains stable shape and phase change activity, has high strength and phase change enthalpy, and can be widely used in the fields of heat storage, warmth and energy storage.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, and in particular to a phase-change heat storage fiber with a composite structure and a preparation method thereof. Background Art
[0002] Synthetic fibers have been widely used in clothing, home textiles, industry, aerospace and other fields. In recent years, with the rapid development of the synthetic fiber industry, the needs of various industries have gradually developed towards functionality, energy saving and high added value. Phase change thermal storage synthetic fiber is an emerging fiber material that achieves energy storage and release based on the absorption or release of heat by the material during the phase change process. It can achieve secondary distribution of energy across time and space. Therefore, at a time when the energy crisis is prominent, it has received extensive research and attention.
[0003] In the existing synthetic fiber production, melt spinning is the key production process for widely used synthetic fiber materials such as polyester, polyamide, polyurethane and polyethylene. It heats the polymer to the melting temperature to achieve the molding of the fiber material. Therefore, its processing temperature is usually >200°C.
[0004] The phase change materials currently in widespread use will turn into liquid at high temperatures, causing leakage. Although related microcapsule technology has been developed, it is difficult to ensure structural stability at high temperatures. Therefore, it is urgent to develop phase change materials suitable for melt spinning technology, so as to further develop composite fibers with phase change functions. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a composite structure phase change thermal storage fiber and a preparation method thereof, so as to solve the problem that traditional phase change microcapsules are difficult to apply to melt spinning process.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The first aspect of the present invention provides a phase-change heat storage fiber with a composite structure, wherein the phase-change heat storage fiber comprises a polymer fiber matrix and a high-entropy vanadium-based shell phase-change nano-microcapsule;
[0008] The high entropy vanadium-based shell phase-change nano-microcapsules are uniformly embedded in the polymer fiber matrix, wherein the polymer fiber matrix accounts for 85-95wt% and the high entropy vanadium-based shell phase-change nano-microcapsules account for 5-15wt%;
[0009] The polymer fiber matrix includes one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide;
[0010] The high entropy vanadium-based shell phase-change nano-microcapsules are composite materials with a core-shell structure;
[0011] The core layer of the high entropy vanadium-based shell phase change nano-microcapsule is a long carbon chain aliphatic hydrocarbon phase change material, and the shell layer is a high entropy vanadium-based phase change material X a V b O c , wherein X is selected from four or more of Ti, Hf, Nb, Tl, Zr, and W, and a is the sum of the stoichiometric numbers of all elements in X, a=b, a+b=c;
[0012] The polyester includes one or more of polyethylene terephthalate, polybutylene terephthalate, and polyarylate.
[0013] Furthermore, the long carbon chain aliphatic hydrocarbon phase change material is selected from one or more of n-octadecane, n-nonadecane, n-eicosane and n-heneicosane, and accounts for 30-90wt% of the mass in the high entropy vanadium-based shell phase change nano-microcapsules;
[0014] The high entropy vanadium-based phase change material X a V b O c The mass proportion in high entropy vanadium-based shell phase change nanocapsules is 10~70wt%.
[0015] Furthermore, the phase change heat storage fiber has a fineness of 30-300 dtex, a strength of >2.3 cN / dtex, a phase change temperature of 20-50°C, a phase change enthalpy value of >15 J / g, and a phase change enthalpy value retention rate of >95% after 1000 cycles of heating and cooling.
[0016] A second aspect of the present invention provides a method for preparing the phase change thermal storage fiber of the composite structure as described above, comprising the following steps:
[0017] 1) Add polysorbate 80 to deionized water and stir thoroughly to mix well. 2 HPO 4 12H 2 After O is melted, it is evenly mixed with the dispersion liquid, and the water phase is obtained after magnetic stirring;
[0018] 2) Add long carbon chain alkanes into the reactor, add sorbitan oleate and stir thoroughly to obtain an oil phase;
[0019] 3) adding the aqueous phase obtained in step 1) into a container containing the oil phase, heating in a water bath environment and stirring thoroughly to obtain a uniformly dispersed water-in-oil emulsion;
[0020] 4) weighing the vanadium source and four or more inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W in a molar ratio, adding them into a mixed solvent, stirring them, and then ball milling them to achieve uniform distribution at the atomic level;
[0021] 5) slowly adding the mixed inorganic source obtained in step 4) into a container containing the water-in-oil emulsion, adding a chelating ligand, and performing high-humidity negative pressure suction to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of the long carbon chain alkane and fully wrapping the core body;
[0022] 6) washing the core-shell nano-microcapsules obtained in step 5) with an ethanol-water mixed solution and drying to obtain high entropy vanadium-based shell phase change nano-microcapsules;
[0023] 7) adding the high entropy vanadium-based shell phase change nano-microcapsules obtained in step 6) and the polymer masterbatch into a twin-screw extruder according to a mass ratio, and obtaining a uniformly mixed composite masterbatch through high-temperature melting, extrusion molding and pelletizing processes;
[0024] 8) After fully drying the composite masterbatch obtained in step 7), add it into the feed funnel of a high-speed melt spinning machine for spinning and drawing to obtain a phase change thermal storage fiber with a composite structure.
[0025] Further, in step 1), the polysorbate 80, deionized water and Na 2 HPO 4 12H 2 The mass ratio of O melt is 0.1:5:20, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes;
[0026] In step 2), the mass ratio of the long carbon chain alkane to sorbitan oleate is 30-40:1, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes.
[0027] Furthermore, in step 3), the water bath temperature is 50-70°C, the stirring speed is 200-500 rpm, and the stirring time is 0.5-3 hours;
[0028] In step 4), the molar ratio of the vanadium source to the four inorganic precursors is 1:0.25:0.25:0.25:0.25, and the ball mill adopts zirconium ball dry milling with a rotation speed of 300-500 rpm and a time of 1-5 hours.
[0029] Further, in step 5), the molar ratio of the vanadium source to the chelating ligand is 1:0.01-0.05;
[0030] The chelating ligand is acetic acid.
[0031] Furthermore, in step 5), the environmental humidity of the high-humidity negative pressure suction is 85-99%, the negative pressure is 0.5-5 MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.
[0032] Furthermore, in step 6), the washing liquid used is a mixed liquid of 50% deionized water and 50% ethanol, the washing times are 3 to 5 times, and after washing, the mixture is centrifuged at a speed of 3000 to 6000 rpm for 10 to 20 minutes;
[0033] The drying temperature is 40-60° C. and the drying time is 0.5-3 hours.
[0034] Further, in step 7), the melt temperature of the twin-screw extruder is 180-320°C, the extruded nascent fibers are solidified in a water bath, and pelletized using a pelletizer;
[0035] In step 8), the drying condition is a gradient temperature increase, the first stage of temperature increase is from room temperature to 80°C over 30 minutes, the second stage of temperature increase is from 80°C to 100-120°C over 30 minutes, and the third stage of temperature increase is from 120-150°C over 1 hour;
[0036] In step 8), the spinning temperature is 180° C. to 320° C., the spinning speed is 500 to 4500 m / min, and the drafting multiple is 1 to 4 times.
[0037] Compared with the prior art, the present invention has the following technical advantages:
[0038] The high entropy vanadium-based shell phase change nano-microcapsules used in the present invention have both an efficient phase change core layer and a high-strength phase change active shell layer. Under the condition of ensuring the shape of the microcapsules and no leakage of effective ingredients, the high enthalpy value of the phase change material (>200J / g) is retained. At the same time, its high temperature can maintain shape stability and phase change activity at an external processing temperature of 200~300℃. The composite structure phase change thermal storage fiber made by mixing it with a polymer matrix has both high strength and phase change enthalpy value (>15J / g), which can be widely used in the fields of thermal storage and energy storage. DETAILED DESCRIPTION
[0039] The present invention develops a phase-change fiber with a composite structure, the fiber includes a polymer matrix and high-entropy vanadium-based shell phase-change nano-microcapsules, the nano-microcapsules are uniformly embedded in the polymer fiber, wherein the polymer content accounts for 85-95wt%, and the high-entropy vanadium-based shell phase-change nano-microcapsules account for 5-15wt%; the polymer includes but is not limited to one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide, and the high-entropy vanadium-based shell phase-change nano-microcapsules are a composite material with a core-shell structure.
[0040] According to claim 1, a composite structure phase change thermal storage fiber, wherein the core layer of the high entropy vanadium-based shell phase change nano-microcapsule is a long carbon chain aliphatic hydrocarbon phase change material, including but not limited to one or more of n-octadecane, n-nonadecane, n-eicosane and n-heneicosane, with a mass ratio of 30 to 90wt%; the shell layer is a high entropy vanadium-based phase change material X a V b O c , wherein X is four or more of Ti, Hf, Nb, Tl, Zr, and W, a is the comprehensive stoichiometric number of all elements in X, a=b, a+b=c, and the mass proportion is 10~70wt%.
[0041] The composite fiber has a fineness of 50~300dtex, a strength of >2.5cN / dtex, a phase change temperature of 20~50℃, a phase change enthalpy value of >15J / g, no obvious phase change hysteresis, a stable fiber shape during the phase change process, no liquid leakage, and excellent recyclability. After 1000 cycles of heating and cooling, the phase change enthalpy value retention rate is >95%.
[0042] A method for preparing a phase-change heat storage fiber of a composite structure, the method comprising the following steps:
[0043] 1) Add polysorbate 80 to deionized water and stir thoroughly to mix well. 2 HPO 4 12H 2 After O is melted, it is evenly mixed with the dispersion liquid, and the water phase is obtained after magnetic stirring;
[0044] 2) Add long carbon chain alkane into a three-necked flask, add sorbitan oleate and stir thoroughly to obtain an oil phase;
[0045] 3) Add the water phase obtained in 1) into the three-necked flask containing the oil phase, heat in a water bath and stir thoroughly to obtain a uniformly dispersed water-in-oil emulsion;
[0046] 4) weighing the vanadium source and four or more inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W in a molar ratio and adding them into a mixed solvent for stirring, followed by high-energy ball milling to achieve uniform distribution at the atomic level;
[0047] 5) slowly adding the mixed inorganic source obtained in 4) into a three-necked flask containing the water-in-oil emulsion, adding a chelating ligand, and performing high-humidity negative pressure suction to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of the long carbon chain alkane and fully wrapping the core body;
[0048] 6) The core-shell nanocapsules obtained in 5) are washed with 50% ethanol and fully dried to obtain high entropy vanadium-based shell phase change nanocapsules.
[0049] 7) adding the high entropy vanadium-based shell phase change nano-microcapsules obtained in 6) and the polymer masterbatch into a twin-screw extruder according to a mass ratio, and obtaining a uniformly mixed composite masterbatch through high-temperature melting, extrusion molding and pelletizing processes;
[0050] 8) After fully drying the composite masterbatch obtained in 7), add it into the feed funnel of a high-speed melt spinning machine for spinning and drawing to obtain a phase change heat storage fiber with a composite structure.
[0051] In step 1), polysorbate 80, deionized water and Na 2 HPO 4 12H 2 The mass ratio of the O melt is 0.1:5:20, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes.
[0052] In step 2), the mass ratio of the long carbon chain alkane to sorbitan oleate is 30-40:1, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes.
[0053] In step 3), the water bath temperature is 50-70° C., the stirring speed is 200-500 rpm, and the stirring time is 0.5-3 hours.
[0054] In step 4), the molar ratio of the vanadium source to the four inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W is 1:0.25:0.25:0.25:0.25, the ball milling is zirconium ball dry milling, the rotation speed is 300-500 rpm, and the time is 1-5 hours.
[0055] In step 5), the molar ratio of the vanadium source to the chelating ligand is 1:0.01-0.05.
[0056] In step 5), the ambient humidity of the high-humidity negative pressure suction is 85~99%, the negative pressure is 0.5~5MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.
[0057] In step 6), the high washing liquid is a mixed liquid of 50% deionized water and 50% ethanol, the washing times are 3 to 5 times, and after washing, the washing is separated by centrifugation at a speed of 3000 to 6000 rpm for 10 to 20 minutes; the drying process temperature is 40 to 60°C for 0.5 to 3 hours.
[0058] In step 7), the melting temperature of the twin-screw extruder is 180-320° C., the extruded nascent fibers are solidified in a water bath, and pelletized by a pelletizer.
[0059] In step 8), the drying condition is a gradient temperature increase, the first stage of temperature increase is from room temperature to 80°C over 30 minutes, the second stage of temperature increase is from 80°C to 100-120°C over 30 minutes, and the third stage of temperature increase is from 120-150°C over 1 hour.
[0060] In step 8), the spinning process temperature is 180°C to 320°C, the spinning speed is 500 to 4500 m / min, and the drafting multiple is 1 to 4 times.
[0061] The particle size of the prepared high-entropy vanadium-based shell phase change nano-microcapsules is 500~800nm, the phase change temperature is 20~50℃, the phase change enthalpy value is >200J / g, there is no obvious phase change hysteresis phenomenon, the shape of the microcapsules is stable during the phase change process, there is no liquid leakage, and it has excellent recyclability. After 1000 heating and cooling cycles, the phase change enthalpy value retention rate is >95%; a composite structure phase change heat storage fiber has a fineness of 30~300dtex, a strength of >2.3cN / dtex, a phase change enthalpy value >15J / g, no obvious phase change hysteresis phenomenon, the fiber shape is stable during the phase change process, there is no liquid leakage, and it has excellent recyclability. After 1000 heating and cooling cycles, the phase change enthalpy value retention rate is >95%.
[0062] The present invention is described in detail below in conjunction with specific embodiments. Any features such as preparation means, materials, structures or composition ratios not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.
[0063] Example 1
[0064] Polysorbate 80, deionized water and Na 2 HPO 4 12H 2The O melt was added to the flask at a mass ratio of 0.1:5:20 and stirred at a speed of 500 rpm. After stirring for 5 minutes, the water phase was obtained. Then, n-octadecane and sorbitan oleate were added to the three-necked flask at a mass ratio of 40:1 and stirred at a speed of 500 rpm. After stirring for 8 minutes, the oil phase was obtained. The water phase was added to the three-necked flask containing the oil phase, and stirred and mixed in a water bath environment. The water bath temperature was 50°C, the stirring speed was 500 rpm, and the time was 1 hour to obtain a uniformly dispersed oil-in-water emulsion. Subsequently, vanadium acetylacetonate, zirconium isopropoxide, titanium isopropoxide, thallium acetate and tungsten chloride were added into a mixed solvent of water and ethanol (volume ratio of 1:4) in a stoichiometric ratio of 1:0.25:0.25:0.25:0.25 and stirred and mixed. At room temperature, the mixture was stirred at a speed of 450 r / min for 4 hours. The mixture was then transferred to a ball mill, and the ratio of the gel mass to the zirconium ball mass was controlled to be 1:100. The mixture was ball milled at a speed of 500 r / min for 4 hours to allow the inorganic sources to form an atomic-level mixture. After the uniformly mixed sol and zirconium balls are separated, they are added to a three-necked flask containing an oil-in-water emulsion, and acetic acid is added at a ratio of one-fiftieth of the vanadium acetylacetonate dosage, and then ethanol / water mixed wet cold air below room temperature (10°C) is passed into the solution at an airflow rate of 80mL / min, and a water pump is used to promote the reaction by negative pressure suction, ensuring that the humidity of the reaction system is ~90%, and the negative pressure is ~2MPa to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of octadecane and fully encapsulating octadecane. The obtained microcapsules are washed with a washing liquid of 50% deionized water and 50% ethanol mixed liquid, and the washing times are 3 times. After washing, they are separated by centrifugation at a centrifugal speed of 6000 rpm for 10 minutes; the temperature of the drying process is 40°C and the time is 3 hours. The obtained high entropy vanadium-based shell phase change nano-microcapsules have a phase change temperature of 28°C, a phase change enthalpy value of >205 J / g, no obvious phase change hysteresis phenomenon, a stable shape of the microcapsules during the phase change process, no liquid leakage, and excellent recyclability. After 1000 heating and cooling cycles, the phase change enthalpy value retention rate is 98.2%. The obtained high entropy vanadium-based shell phase change nano-microcapsules are mixed with polyester masterbatch at a mass ratio of 1:20 and extruded and granulated by a metering twin screw. The twin screw melting temperature is: 260°C in the first zone, 275°C in the second zone, 290°C in the third zone, 300°C in the fourth zone, 305°C in the fifth zone, and 310°C in the sixth zone. The screw extrusion speed is 6m / min. The extruded primary fiber is solidified and formed in tap water at a water temperature of 25°C. The speed of the pelletizer is 6m / min. The obtained mixed masterbatch was vacuum dried in a drum oven. The drying process was as follows: the first stage of heating was from room temperature to 80°C over 30 minutes, the second stage of heating was from 80°C to 120°C over 30 minutes, the third stage of heating was from 150°C over 1 hour, and the drying was continued for 20 hours.The dried masterbatch is melt-spun, and the spinning process has a temperature of 260°C to 320°C, a spinning speed of 4200 m / min, and a drafting multiple of 2.5 times. The prepared composite phase change thermal storage fiber has a fineness of 125 dtex, a strength of >2.6 cN / dtex, and a phase change enthalpy of 16.2 J / g.
[0065] Example 2
[0066] Polysorbate 80, deionized water and Na 2 HPO 4 12H 2The O melt was added to the flask at a mass ratio of 0.1:5:20 and stirred at a speed of 500 rpm. After stirring for 5 minutes, the water phase was obtained. Then, n-eicosane and sorbitan oleate were added to the three-necked flask at a mass ratio of 35:1 and stirred at a speed of 500 rpm. After stirring for 8 minutes, the oil phase was obtained. The water phase was added to the three-necked flask containing the oil phase, and stirred and mixed in a water bath environment. The water bath temperature was 50°C, the stirring speed was 500 rpm, and the time was 1 hour to obtain a uniformly dispersed oil-in-water emulsion. Subsequently, vanadium acetylacetonate, zirconium isopropoxide, hafnium isopropoxide, thallium acetate and tungsten chloride were added into a mixed solvent of water and ethanol (volume ratio of 1:4) in a stoichiometric ratio of 1:0.25:0.25:0.25:0.25, and stirred and mixed. At room temperature, the mixture was stirred at a speed of 450 r / min for 4 hours. The mixture was then transferred to a ball mill, and the ratio of the gel mass to the zirconium ball mass was controlled to be 1:100. The mixture was ball milled at a speed of 500 r / min for 4 hours to allow the inorganic sources to form an atomic-level mixture. After the uniformly mixed sol and zirconium balls are separated, they are added to a three-necked flask containing an oil-in-water emulsion, and acetic acid is added at a ratio of one-fiftieth of the acetylacetonate vanadium stoichiometry. Subsequently, ethanol / water mixed wet cold air below room temperature (10°C) is passed into the solution at an airflow rate of 80mL / min, and a water pump is used to promote the reaction by negative pressure suction, ensuring that the humidity of the reaction system is ~90%, and the negative pressure is ~2MPa to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of eicosane and fully encapsulating octadecane. The obtained microcapsules are washed with a washing liquid of 50% deionized water and 50% ethanol mixed liquid, and the washing times are 3 times. After washing, they are centrifuged at a centrifugal speed of 6000 rpm for 10 minutes; the temperature of the drying process is 40°C and the time is 3 hours. The obtained high entropy vanadium-based shell phase change nano-microcapsules have a phase change temperature of 37°C, a phase change enthalpy value of >212 J / g, no obvious phase change hysteresis phenomenon, a stable shape of the microcapsules during the phase change process, no liquid leakage, and excellent recyclability. After 1000 heating and cooling cycles, the phase change enthalpy value retention rate is 97.5%. The obtained high entropy vanadium-based shell phase change nano-microcapsules are mixed with polyester masterbatch at a mass ratio of 1:20 and extruded and granulated by a metering twin screw. The twin screw melting temperature is: 260°C in the first zone, 275°C in the second zone, 290°C in the third zone, 300°C in the fourth zone, 305°C in the fifth zone, and 310°C in the sixth zone. The screw extrusion speed is 8m / min. The extruded primary fiber is solidified and formed in tap water at a water temperature of 25°C. The speed of the pelletizer is 8m / min. The obtained mixed masterbatch was vacuum dried in a drum oven. The drying process was as follows: the first stage of heating was from room temperature to 80°C over 30 minutes, the second stage of heating was from 80°C to 120°C over 30 minutes, the third stage of heating was from 150°C over 1 hour, and the drying was continued for 20 hours.The dried masterbatch is melt-spun, and the spinning process has a temperature of 260°C to 320°C, a spinning speed of 3800 m / min, and a draft ratio of 2.5 times. The prepared polymer / high-entropy carbon-based composite fiber has a fineness of 108 dtex, a strength of 2.5 cN / dtex, and a phase change enthalpy of 16.8 J / g.
[0067] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A phase-change heat storage fiber with a composite structure, characterized in that: The phase-change heat storage fiber comprises a polymer fiber matrix and a high-entropy vanadium-based shell phase-change nano-microcapsule; The high entropy vanadium-based shell phase-change nano-microcapsules are uniformly embedded in the polymer fiber matrix, wherein the polymer fiber matrix accounts for 85-95wt% and the high entropy vanadium-based shell phase-change nano-microcapsules account for 5-15wt%; The polymer fiber matrix includes one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide; The high entropy vanadium-based shell phase-change nano-microcapsules are composite materials with a core-shell structure; The core layer of the high entropy vanadium-based shell phase change nano-microcapsule is a long carbon chain aliphatic hydrocarbon phase change material, and the shell layer is a high entropy vanadium-based phase change material X a V b O c , wherein X is selected from four or more of Ti, Hf, Nb, Tl, Zr, and W, and a is the sum of the stoichiometric numbers of all elements in X, a=b, a+b=c; The polyester includes one or more of polyethylene terephthalate, polybutylene terephthalate, and polyarylate.
2. The phase-change heat storage fiber of the composite structure according to claim 1, characterized in that: The long carbon chain aliphatic hydrocarbon phase change material is selected from one or more of n-octadecane, n-nonadecane, n-eicosane and n-heneicosane, and accounts for 30-90wt% of the mass in the high entropy vanadium-based shell phase change nano-microcapsules; The high entropy vanadium-based phase change material X a V b O c The mass proportion in high entropy vanadium-based shell phase change nanocapsules is 10~70wt%.
3. The phase-change heat storage fiber with a composite structure according to claim 1, characterized in that: The phase change heat storage fiber has a fineness of 30-300 dtex, a strength of >2.3 cN / dtex, a phase change temperature of 20-50°C, a phase change enthalpy value of >15 J / g, and a phase change enthalpy value retention rate of >95% after 1000 heating and cooling cycles.
4. A method for preparing a phase-change heat storage fiber with a composite structure as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Add polysorbate 80 into deionized water and stir thoroughly to mix evenly, melt Na2HPO4·12H2O and mix evenly with the dispersion, and obtain an aqueous phase after magnetic stirring; 2) Add long carbon chain alkanes into the reactor, add sorbitan oleate and stir thoroughly to obtain an oil phase; 3) adding the aqueous phase obtained in step 1) into a container containing the oil phase, heating in a water bath environment and stirring sufficiently to obtain a uniformly dispersed water-in-oil emulsion; 4) weighing the vanadium source and four or more inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W in a molar ratio, adding them into a mixed solvent, stirring them, and then ball milling them to achieve uniform distribution at the atomic level; 5) slowly adding the mixed inorganic source obtained in step 4) into a container containing the water-in-oil emulsion, adding a chelating ligand, and performing high-humidity negative pressure suction to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of the long carbon chain alkane and fully wrapping the core body; 6) washing the core-shell nano-microcapsules obtained in step 5) with an ethanol-water mixed solution and drying to obtain high entropy vanadium-based shell phase change nano-microcapsules; 7) adding the high entropy vanadium-based shell phase change nano-microcapsules obtained in step 6) and the polymer masterbatch into a twin-screw extruder according to a mass ratio, and obtaining a uniformly mixed composite masterbatch through high-temperature melting, extrusion molding and pelletizing processes; 8) After fully drying the composite masterbatch obtained in step 7), add it into the feed funnel of a high-speed melt spinning machine for spinning and drawing to obtain a phase change thermal storage fiber with a composite structure.
5. The method for preparing a composite phase-change heat storage fiber according to claim 4, characterized in that: In step 1), the mass ratio of polysorbate 80, deionized water and Na2HPO4·12H2O melt is 0.1:5:20, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes; In step 2), the mass ratio of the long carbon chain alkane to sorbitan oleate is 30-40:1, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes.
6. The method for preparing a composite phase-change heat storage fiber according to claim 4, characterized in that: In step 3), the water bath temperature is 50-70°C, the stirring speed is 200-500 rpm, and the stirring time is 0.5-3 hours; In step 4), the molar ratio of the vanadium source to the four inorganic precursors is 1:0.25:0.25:0.25:0.25, and the ball mill adopts zirconium ball dry milling with a rotation speed of 300-500 rpm and a time of 1-5 hours.
7. The method for preparing a composite phase-change heat storage fiber according to claim 4, characterized in that: In step 5), the molar ratio of the vanadium source to the chelating ligand is 1:0.01-0.05; The chelating ligand is acetic acid.
8. The method for preparing a composite phase-change heat storage fiber according to claim 4, characterized in that: In step 5), the environmental humidity of the high-humidity negative pressure suction is 85-99%, the negative pressure is 0.5-5 MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.
9. The method for preparing a composite phase-change heat storage fiber according to claim 4, characterized in that: In step 6), the washing liquid used is a mixed liquid of 50% deionized water and 50% ethanol, the washing times are 3 to 5 times, and after washing, the mixture is centrifuged at a speed of 3000 to 6000 rpm for 10 to 20 minutes; The drying temperature is 40-60° C. and the drying time is 0.5-3 hours.
10. The method for preparing a composite phase-change thermal storage fiber according to claim 4, characterized in that: In step 7), the melt temperature of the twin-screw extruder is 180-320°C, the extruded nascent fibers are solidified in a water bath, and pelletized by a pelletizer; In step 8), the drying condition is a gradient temperature increase, the first stage of temperature increase is from room temperature to 80°C over 30 minutes, the second stage of temperature increase is from 80°C to 100-120°C over 30 minutes, and the third stage of temperature increase is from 120-150°C over 1 hour; In step 8), the spinning temperature is 180° C. to 320° C., the spinning speed is 500 to 4500 m / min, and the drafting multiple is 1 to 4 times.
Citation Information
Patent Citations
Preparing method for heat storing and temperature adjusting phase change microcapsules
CN105838334A
Heat storage constant temperature fiber preparation method and method for preparing fabric from heat storage constant temperature fiber
CN107022801A